Optical (DRUV-VIS) and magnetic (EPR) behavior of synthetic melanins - Júlio César Pereira dos Santos; Cláudia Eliana Bruno Marino; Antonio Salvio Mangrich; Edivaltrys Inayve Pissinati de Rezende (Materials Research, 2012)
The properties of melanins prepared from L-dopa oxidation by both chemical and electrochemical methods are reported, searching for a material with more intense optical absorption in the visible region. The characterization of the samples have been done by cyclic voltammetry (CV), cronoamperometry (CA), Fourier transformed infrared spectroscopy (FTIR), electron paramagnetic resonance spectroscopy (EPR) and diffuse reflectance ultraviolet-visible spectroscopy (DRUV-VIS) techniques. The electrochemical method enhanced the organic free radical (spin) concentration and the absorption intensity in the visible region of the spectrum. The DRUV-VIS technique along with mathematical tools, such as the Kubelka-Munk remission function, were good options for the characterization of the final products.